1968
DOI: 10.1002/jez.1401670106
|View full text |Cite
|
Sign up to set email alerts
|

Heart induction in salamanders

Abstract: Heart determination is a gradual, cumulative process involving inductive and suppressive interactions between the heart mesoderm and nearby embryonic tissues. Our analysis of heart determination in the California newt, Taricha torosa, includes defect and other i n vivo experiments, and explants in epidermal vesicles and into hanging drops.Explants of presumptive heart mesoderm from neurulae into hanging drops of a completely defined salt solution (Niu-Twitty solution) produce beating hearts only infrequently. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…Our experiments also cannot rule out a potential inductive role of endoderm prior to stage 4 + . Although this question has been addressed in anurans and urodeles by removing endoderm from successively younger embryos (Nieuwkoop, 1947;Jacobson, 1960Jacobson, ,1961Jacobson and Duncan, 1968;Sater and Jacobson, 1990a), our results concerning the timing of PCM specification and recent fate mapping studies suggest that this approach may not be feasible in birds. Cells destined to form the heart pass through the primitive streak during stage 3a-b (Garcia-Martinez and , approximately coincident with the movement of endodermal cells through the streak and displacement of the hypoblast rostrally.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our experiments also cannot rule out a potential inductive role of endoderm prior to stage 4 + . Although this question has been addressed in anurans and urodeles by removing endoderm from successively younger embryos (Nieuwkoop, 1947;Jacobson, 1960Jacobson, ,1961Jacobson and Duncan, 1968;Sater and Jacobson, 1990a), our results concerning the timing of PCM specification and recent fate mapping studies suggest that this approach may not be feasible in birds. Cells destined to form the heart pass through the primitive streak during stage 3a-b (Garcia-Martinez and , approximately coincident with the movement of endodermal cells through the streak and displacement of the hypoblast rostrally.…”
Section: Discussionmentioning
confidence: 81%
“…In urodeles, endoderm influences heart development first through the initial inductive influence required for the establishment of PCM and subsequently via "formative influences" that increase the degree of heart muscle cell differentiation and heart tube formation (Mangold, 1954(Mangold, , 1956Holtfreter and Hamburger, 1955;Jacobson, 1960Jacobson, ,1961. In Taricha torosa, anterolateral endoderm (and homogenates of endoderm) also increases the rate of heart formation, as assayed by the initiation of heartbeat (Jacobson and Duncan, 1968). Our results show that anterolateral endoderm influences several aspects of heart development in quail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies across various species have demonstrated that interactions between endoderm and overlying mesoderm are involved in cardiac differentiation (Orts Llorca 1963;Jacobson and Duncan 1968;Sugi and Lough 1994;Nascone and Mercola 1995;Schultheiss, Xydas et al 1995) and, more specifically, play an inductive role as evidenced by the generation of beating cardiac tissue in cocultures of non-cardiogenic embryonic tissue explants and endodermal tissue (Schultheiss, Xydas et al 1995). The inductive characteristic of the endoderm can be attributed to TGF-β superfamily and FGF family growth factors, expressed by anterior lateral endoderm, that have been reported to be involved in cardiac differentiation.…”
Section: Inductive Signals From the Anteriolateral(embryogenesis)/primentioning
confidence: 99%
“…Despite this, studies in which anterior (pharyngeal) endoderm was removed or transplanted have provided evidence that these cells have an instructive or permissive role in embryonic cardiogenesis (reviewed by Jacobson and Sater, 1988). For example, in several urodele species, removal of endoderm from neurula-stage embryos has been shown to prevent heart formation (Jacobson, 1960(Jacobson, , 1961Jacobson and Duncan, 1968;Fullilove, 1970). Moreover, normal anterior endoderm has been shown to induce myofibrillogenesis and contractility in pre-cardiac mesoderm explanted from mutant salamanders which exhibit abnormal cardiac development (Lemanski et al, 1979).…”
Section: Introductionmentioning
confidence: 99%